Bazedoxifene effects on osteoprotegerin, insulin-like growth factor, tumor necrosis factor and bone mineral density - Ma, Yonggang; Chai, Zhen; Ren, Longlong; Hu, Qiaolong (Cellular and Molecular Biology, 2020)
To observe the clinical effect of estrogenic drugs (Bazedoxifene) on bone targeting in the treatment of osteoporosis and explore its mechanism. Methods:112 patients with postmenopausal osteoporosis who received Bazedoxifene drugs in our hospital from January to December 2018 were collected as a study group, and 56 patients treated with calcium alone were collected as a control group. the risk of adverse events such as bone mineral density, osteoprotegerin (OPG), insulin-like growth factor (IGF), tumor necrosis factor (TNF-Î±), and fracture after treatment were analyzed before and after treatment. Results: There was no significant difference in the mean lumbar positive position (L2-4) and right femoral neck bone density and OPG, IGF, TNF-Î± level between the two groups before treatment (P>0.05). The total effective rate of clinical treatment in the study group was 88.39%, the control group was 23.21%, the difference between the two groups was statistically significant (PË‚0.05). After treatment, the mean lumbar positive position (L2-4) and the right femoral neck bone density and OPG, IGF in the study group were higher than those in the control group, lower than those in the control group (P<0.05). the occurrence of adverse events such as fracture, spinal deformation and fatigue in the study group after 12 months of treatment was significantly lower than that in the control group (P<0.05), but there was no significant difference in the occurrence of hot flashes and venous thromboembolism between the two groups (P>0.05). Conclusion: Bazedoxifene is an effective drug for the treatment of postmenopausal osteoporosis. It can not only prevent the rapid loss of bone mass, effectively relieve the symptoms of menopause, but also improve bone density and reduce the risk of fracture.